Shape and Size Variations in the Astragalus of Large and Small Bovids - Unal, Burak; Guzel, Baris Can; Cakar, Buket; Kanmaz, Yesim Aslan; Yigit, Funda; Gundemir, Ozan; Spataru, Mihaela-Claudia (Mdpi, 2025)
The astragalus acts as a crucial intermediary in the tarsal joint, facilitating the transfer of body weight to the lower extremities while also ensuring both stability and mobility through its articulation with adjacent bones, enabling efficient movement. This study investigates the morphological diversity of the astragalus in three modern cattle breeds, one goat breed, and three sheep breeds using three-dimensional geometric morphometric methods. A total of 225 specimens were analyzed in this study. Large bovids, such as the Holstein and Simmental cattle breeds, had a more developed lateral edge of the proximal trochlea and a more rounded astragalus. In small bovids, the Akkaraman and Morkaraman sheep breeds displayed a more prominent medial edge and a rounded astragalus form, while the Hair goat breed exhibited a rectangular structure with a well-developed lateral projection. The results of this study demonstrate that the astragalus serves as a reliable morphological marker for differentiating between large and small bovids, as well as between closely related taxa such as sheep and goats. These shape variations, particularly observed in the proximal trochlea, reflect functional adaptations to size, body mass, and locomotor demands, making the astragalus a critical element for taxonomic identification and biomechanical analysis.
Keywords: geometric morphometrics; shape analysis; talus; taxonomy; veterinary anatomy